The Effect of Financial Education on Increasing Financial Literacy - Krisda Pebriani Hulu; Maria Magadalena Bate’e; Sophia M, Kakisina; Kurniawan S. Zai (Manunggal Halim Jaya, 2024)
That financial literacy is part of economic literacy that is important to develop through educational activities. Financial literacy is very important especially for individuals because this financial aspect is a determinant in finding individual life needs. although there are still individuals who have not implemented good financial literacy in their lives. As is the case with students of SMK Negeri 1 Tugala Oyo which is one of the vocational schools in Tugala Oyo District, North Nias Regency. This study aims to determine how much influence Financial Education has on improving Financial Literacy at SMK N 1 Tugala Oyo, North Nias Regency. This study uses a quantitative method, respondents are students of SMK Negeri 1 Tugala Oyo as many as 65 people, where researchers collect data using questionnaires, then conduct validity studies, and data reliability tests, correlation coefficients, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), simple linear regression, coefficient of determination, and t-test. The results of the study showed that the influence of financial education on increasing financial literacy at SMK Negeri 1 Tugala Oyo was 22.4% and 77.6% was influenced by other factors that were not influenced by this study.